Effects of iRoot BP and white mineral trioxide aggregate on cell viability and the expression of genes associated with mineralization. (12th November 2014) - Öncel Torun, Z.; Torun, D.; Demirkaya, K.; Yavuz, S. T.; Elçi, M. P.; Sarper, M.; Avcu, F.
Abstract Aim To evaluate the cytotoxicity and mineralization effects of iRoot BP in human dental pulp cells (hDPCs) and to compare them with those of white mineral trioxide aggregate (WMTA). Methodology hDPCs were exposed to prepared dilutions (1 : 1–1 : 10) of the test materials. Cell viability was evaluated using the XTT assay after incubation periods of 24, 48 or 72 h. The expression of mineralization‐related genes (bone morphogenic protein, osteonectin, bone sialoprotein, osteopontin, dentine sialophosphoprotein and collagen type 1) and heme oxygenase 1 was measured by quantitative real‐time polymerase chain reaction (qRT‐PCR) at 24 and 72 h. Statistical differences between test materials were analysed with the Mann–Whitney test. Results The 1 : 1 and 1 : 2 dilutions of iRoot BP were associated with higher cell viability after 24 h (P < 0.05). Only the 1 : 1 dilution of iRoot BP had higher cell viability after 48 h (P < 0.05), and there was no difference between iRoot BP and WMTA after 72 h (P > 0.05). Although somewhat variable, according to the gene expression results, iRoot BP had a mineralization potential similar to that of WMTA. WMTA revealed a higher heme oxygenase 1 (HO‐1) mRNA level than iRoot BP (P < 0.001). Conclusions iRoot BP and WMTA were biocompatible and facilitated odontoblastic differentiation of hDPCs.